Pengaruh Pemberian Ekstrak Etanol 70% Daun Binahong (Anredera Cordifolia (Ten.) Steenis) Terhadap Waktu Perdarahan (Bleeding Time) Pada Mencit Jantan Galur Swiss - Kustriyono, Riani Nazila, Riandini Aisyah, S.Si, M.Sc (2017)
Background: Binahong leaves contains flavonoids and tanin. Based on theory, flavonoid and tanin have an effect as agent of hemostatics. Objective: This research is aimed to know the effects of 70% ethanol extract of Binahong leaves on bleeding time in male Swiss strain mice. Methods: This research is an experimental laboratory method with Post Test Only With Control Group Design. The animals that used were 25 male Swiss strain mice 2-3 months old, 20-30 g weight, and were divided into 5 groups: negative control, positive control, the first, second and third treatment group. Bleeding time of each group was calculated by using the Duke method. The data was analyzed with one-way ANOVA test and LSD test.Results: The 70% Ethanolic extract of Binahong leaves with concentration of 10%, 15%, and 20% can decrease bleeding time with mean value of bleeding time were 138.60 ± 19,6 seconds, 127.40 ± 13,8 seconds and 108.20 ± 9,4 seconds respectively. One-way ANOVA test showed that there were significantly differences of bleeding time in the five groups after given treatment, p = 0.000 (p<0.05). Conclusion: The 70% Ethanolic extract of Binahong leaves concentrate of 10%, 15%, and 20% shorten bleeding time on male Swiss strain mice. On this research extract with concentrate 20% has the best effect on shorten bleeding time.